1994
DOI: 10.1007/bf02880810
|View full text |Cite
|
Sign up to set email alerts
|

New age constraints on the cooling and unroofing history of the Trans-Himalayan Ladakh Batholith (Kargil area), N. W. India

Abstract: Thermotectonic history of the Trans-Himalayan Ladakh Batholith in the Kargil area, N. W. India, is inferred from new age data obtained here in conjunction with previously published ages. Fission-track (FT) ages on apatite fall around 20 + 2 Ma recording cooling tM:ough temperatures of ~ 100~ and indicating an unroofing of 4 km of the Ladakh Range since the Early Miocene. Coexisting apatite and zircon FT ages from two samples in Kargil show the rocks to have cooled at an average rate of 5-6~ in the past 40 Ma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…New zircon FT ages (OWM = 43.0  0.5 Ma, Table 2) constrain its low-temperature cooling history (Figure 3 a). When ZFT ages from the Kargil pluton are taken into consideration 46 ( Supplementary Table 1), the batholiths yields an overall single uniform ZFT age population. 45 and published FT data, and zircon and apatite (U-Th)/He (ZHe, AHe) ages 21,22 of the LB and the Deosai Batholith in the west 20 .…”
Section: Cooling History Of Lbmentioning
confidence: 99%
“…New zircon FT ages (OWM = 43.0  0.5 Ma, Table 2) constrain its low-temperature cooling history (Figure 3 a). When ZFT ages from the Kargil pluton are taken into consideration 46 ( Supplementary Table 1), the batholiths yields an overall single uniform ZFT age population. 45 and published FT data, and zircon and apatite (U-Th)/He (ZHe, AHe) ages 21,22 of the LB and the Deosai Batholith in the west 20 .…”
Section: Cooling History Of Lbmentioning
confidence: 99%
“…U-Pb crystallisation ages from the main Batholith range from 65 to 49 Ma , suggesting that magmatism was contemporaneous with the Gangdese Batholith (Scharer et al, 1984) and that magmatic activity ceased with the collision of India and Eurasia. Apatite fission track (AFT) ages of the Ladakh Batholith from Kargil to Chumatang range from 28 to 4.8 Ma (Choubey, 1987;Sorkhabi et al, 1994;Clift et al, 2002;Schlup et al, 2003). The young Pliocene ages are related to minor faulting (Choubey, 1987), however, there remains a spread in single AFT ages from 18 to 28 Ma (Sorkhabi et al, 1994;Clift et al, 2002).…”
Section: Regional Settingmentioning
confidence: 99%
“…Apatite fission track (AFT) ages of the Ladakh Batholith from Kargil to Chumatang range from 28 to 4.8 Ma (Choubey, 1987;Sorkhabi et al, 1994;Clift et al, 2002;Schlup et al, 2003). The young Pliocene ages are related to minor faulting (Choubey, 1987), however, there remains a spread in single AFT ages from 18 to 28 Ma (Sorkhabi et al, 1994;Clift et al, 2002). How these ages record the detailed history of exhumation of the Batholith is not clear due to the broad scatter of the samples.…”
Section: Regional Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The pioneering geochronological studies by Honegger et al (1982) showed that the magmatism started at least 100 Ma ago and continued till the continent-continent collision. Later studies indicated that the span of the plutonic magmatism may range from 100 to 40 Ma ago (Reuber, 1989;Sharma, 1990;Sorkhabi et al, 1994;Weinberg and Dunlap, 2000;Kohn and Parkinson, 2002;Guillot et al, 2003). Recent studies reported Ar-Ar plateau-age of 29.8 ± 0.2 Ma of muscovite from a leucogranite in Ladakh batholith indicating younger post-collision magmatism due to intra-crustal melting at the base of thickened crust in otherwise subduction related batholith (Bhutani et al, 2004).…”
Section: Introductionmentioning
confidence: 99%